TCR signal quality modulates fate decisions of single CD4+ T cells in a probabilistic manner - Cho, Yi-Li; Höfer, Thomas (Cell reports, 2017)
Summary To what extent the lineage decisions of activated CD4+ T cells are determined by the quality of T cell receptor (TCR) ligation is incompletely understood. Here, we show that individual T cells expressing identical TCRs take highly variable fate decisions despite binding the same ligand. We identify a mathematical model that correctly captures this probabilistic behavior and allows one to formalize changes in TCR signal quality—due to cognate versus altered peptide ligation—as changes of lineage-specific proliferation and differentiation rates. We show that recall responses also adhere to this probabilistic framework requiring recruitment of multiple memory clones to provide reliable differentiation patterns. By extending our framework to simulate hypothetical TCRs of distinct binding strength, we reconstruct primary and secondary response patterns emerging from a polyclonal TCR repertoire in silico. Collectively, these data suggest that individual T cells harboring distinct TCRs generate overlapping primary differentiation patterns that segregate only upon repetitive immunization.
Gesehen am 16.07.2018